INFLUENCE OF SPRAYING BY SOME PLANT GROWTH REGULATORS ON DATE PALM SALT TOLERANCE ENHANCEMENT - & et al., Al-Sahaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted to study the impact of foliar spraying by some plant growth regulators to increase salts tolerance of date palm (Phoenix dactylifera L.) cv. Shakar. Thirty young date palm trees (seven years old) and same number of fruiting trees (18 years old) were selected and spraying with naphthalene acetic acid (NAA) solutions at the concentrations (0.50, 100 and 150 ppm), Salicylic acid (0, 0.25, 0.50, and 1.0 mM) and putrescine (0, 0.025, 0.050, 0.1 mM). Results indicated that the application of growth regulators led to reduction trunk diameter comparing with control (121.33 cm). Spraying NAA with concentration of 100 ppm, gave the highest height of the offshoots and a significant difference from the rest of the treatments (253.70 cm). Spraying putrescine with 1.0 mM concentration led to a significant increase in the number of leaves (fronds) as it increased to 24.33 leaf/offshoot, and leaf area which reached 691 cm2. Application of 0.25 mM Salisylic acid increased the number of bunches under saline conditions amounted to 12.67 bunch as well as increased the weight of the fruit to 8.82 g, which differed significantly from the control which gave 7.37 g. As for the size of the fruit, it was found that Spraying of NAA with 100 ppm led to increase the size of the fruit under saline conditions (8.67 cm). We can conclude that the spraying date palm with the above plant growth regulators under saline conditions can lead to increasing absorption of nutrients and subsequent growth and yield improvement.